(untitled) (London Journal of Medical and Health Research, 2024)
Objectives: Primary percutaneous coronary intervention (pPCI) is being increasingly done as the treatment of acute ST elevation myocardial infarction (STEMI). Time until treatment is paramount in the management of STEMI. But the total ischemic time before pPCI how much influencing the outcome is a matter of interest. So we evaluated the influence of total ischemic time on myocardial reperfusion and short term clinical outcome in patients with STEMI treated with primary PCI. Methods: This prospective observational study was conducted from August 2017 to July 2018 in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka. Forty eight (48) acute STEMI patients were selected by purposive sampling based on inclusion and exclusion criteria dividing into two groups as short total ischemic time in whom pain to pPCI time was <6 hours and long total ischemic time in whom pain to pPCI time was 6-12 hours. Angiographic (TIMI flow grade 3 & MBG 3) & short term clinical outcome (MACE, heart failure, major bleeding, minor bleeding, cardiogenic shock, significant arrhythmia, instent thrombosis) were observed and compared between these two groups. Results: The 30-day mortality & morbidity were assessed and compared between short and long total ischemic time before pPCI. The overall 30-day mortality rate was 4.2%, heart failure was 6.2%, cardiogenic shock was 4.2%, major bleeding was 2.1% and minor bleeding was 14.6%. Mortality and morbidity were higher in longer ischemic time group than shorter ischemic time group. In multivariate regression analysis, the factors independently influencing the adverse short term outcome were advance age (OR 1.51, 95% CI 1.105 to 4.101, p=0.03), hypertension (OR 2.44, 95% CI 1.102 to 4.281, p=0.02), diabetes mellitus (OR 2.51, 95% CI 1.200 to 4.987, p=0.02), anterior MI (OR 1.38, 95% CI 1.001 to 2.872, p=0.03), multivessel disease (OR 2.35, 95% CI 1.010 to 5.371, p=0.02), pain to door time (OR 1.66, CI 1.099 to 2.2.722, p=0.04), and total ischemic time (OR 2.67, 95% CI 1.122 to 5.784, p=0.02). Even after correction for predictive baseline and procedural variables of the univariate analysis, longer total ischemic time was the most significant independent predictor (OR 2.67, p=0.02) of short term adverse outcome of primary PCI. Conclusion: According to this study finding, there is prognostic implication of total ischemic time in patients with STEMI undergoing primary PCI. Therefore, all efforts should be made to shorten total ischemic time, including reduction in patient related delays, to improve clinical outcome of STEMI patients.